Colouring one's canvas with compassion - evaluating slow art plus as a means for fostering self-compassion: insights from an art-based gallery intervention - Chia, Charis (Nanyang Technological University, 2023)
Engaging in negative thoughts or self-criticism can exhaust one’s mental and emotional well-being. To combat this negativity, it is essential to practise self-compassion. Through several studies, art has illustrated to be a valuable tool in cultivating self-compassion by providing a space for self-expression, emotional processing, and connection with others. With a dearth of research on such art-based interventions present in Singapore focusing on developing self-care capacities, this study aims to close this gap by investigating the efficacy of Slow Art Plus (SAP), an art-based intervention incorporating mindfulness and self-compassion elements in Singapore, in fostering an individual’s self-compassion.